Surgical Rope for Extracapsular Stabilization of the Knee in Dogs - Ex Vivo Model - Bello, Lucas; Mallmann Pozzobon, Franciéli; da Silva Reinstein, Rainer; Augusto Rovêda, Rainier; Veloso Brun, Maurício; Curvello de Mendonça Müller, Daniel (Acta Scientiae Veterinariae, 2024)
Background: Numerous methods have been documented for the surgical rectification of cranial cruciate ligament deficiency in dogs, including intracapsular and extracapsular procedures and osteotomies. Notably, among the extracapsular techniques, the fabellotibial suture is used for small dogs, while the TightRope fiber tape system is employed for medium, large, and giant dogs. This study aimed to standardize a modified TightRope technique using polyester surgical rope number 1 for the correction of cranial cruciate ligament rupture in dogs. Materials, Methods& Results: This study evaluated tibial compression, drawer movement, and caudal displacement of the femur on x-ray at 4 distinct stages (intact ligament, failed ligament, repair with fabellotibial sutures, and repair with a TightRope modification using polyester surgical rope number 1 in 8 ex vivo canine pelvic limbs. Surgical cords were created using 2 sutures per kilogram of the patient's weight. The final diameters of the cords were evaluated, and the results confirmed the feasibility of the implant thickness. No significant differences were observed in drawer movement and tibial compression between the intact ligament and post-surgical restorations. However, both drawer movement and tibial compression were significantly higher (P < 0.05) following the failure of the cranial cruciate ligament compared to other stages. The weight of the cadavers did not significantly influence (P > 0.05) the drawer movement, tibial compression, or caudal displacement of the femur on x-ray. The extracapsular surgical cord success fully stabilized the knee, as there were no statistically significant differences in drawer movements and tibial compression compared to the lateral fabellotibial suture technique and the intact ligament. This indicates that both tested techniques effectively restore physiological joint stability when assessed with drawer movement and tibial compression. Discussion: Both techniques examined in this study yielded physiological joint stability for drawer movement and tibial compression. However, the modified TightRope technique utilizes more isometric points, facilitating a normal joint range of motion and reduced joint tension. The stabilization achieved with TightRope Fiber Tape is comparable to that of tibial plateau leveling osteotomy in terms of limb function and progression of degenerative joint disease. The primary drawback of this implant is its limited accessibility compared to the equipment used for osteotomies. The potential use of surgical ropes, custom-made from universally available surgical sutures (polyester number 1), significantly enhances the accessibility of the modified TightRope Fiber Tape technique. The cranial cruciate ligament in dogs can withstand 48.07 N ± 0.41 per kilogram of weight before rupturing. Research indicates that the use of number 1 polyester surgical cords allows for the estimation of force increase for each suture added to the implant (25.339 N). Consequently, an implant with traction resistance equivalent to the patient’s intact ligament can be created, irrespective of size and weight. Conclusively, knee stabilization using surgical polyester rope number 1 in the “modified TightRope Fiber Tape” technique proves effective in an ex vivo dog model. We recommend further studies on living patients and long-term postoperative follow-ups. Keywords: implants, cranial cruciate ligament, polyester, TightRope.